Systematics of Miocene apes: State of the art of a neverending controversy. Issue 175 (February 2023) - Urciuoli, Alessandro; Alba, David M.
Abstract: Hominoids diverged from cercopithecoids during the Oligocene in Afro-Arabia, initially radiating in that continent and subsequently dispersing into Eurasia. From the Late Miocene onward, the geographic range of hominoids progressively shrank, except for hominins, which dispersed out of Africa during the Pleistocene. Although the overall picture of hominoid evolution is clear based on available fossil evidence, many uncertainties persist regarding the phylogeny and paleobiogeography of Miocene apes (nonhominin hominoids), owing to their sparse record, pervasive homoplasy, and the decimated current diversity of this group. We review Miocene ape systematics and evolution by focusing on the most parsimonious cladograms published during the last decade. First, we provide a historical account of the progress made in Miocene ape phylogeny and paleobiogeography, report an updated classification of Miocene apes, and provide a list of Miocene ape species-locality occurrences together with an analysis of their paleobiodiversity dynamics. Second, we discuss various critical issues of Miocene ape phylogeny and paleobiogeography (hylobatid and crown hominid origins, plus the relationships of Oreopithecus ) in the light of the highly divergent results obtained from cladistic analyses of craniodental and postcranial characters separately. We conclude that cladistic efforts to disentangle Miocene ape phylogeny are potentially biased by a long-branch attraction problem caused by the numerous postcranial similarities shared between hylobatids and hominids—despite the increasingly held view that they are likely homoplastic to a large extent, as illustrated by Sivapithecus and Pierolapithecus —and further aggravated by abundant missing data owing to incomplete preservation. Finally, we argue that—besides the recovery of additional fossils, the retrieval of paleoproteomic data, and a better integration between cladistics and geometric morphometrics—Miocene ape phylogenetics should take advantage of total-evidence (tip-dating) Bayesian methods of phylogenetic inference combining morphologic, molecular, and chronostratigraphic data. This would hopefully help ascertain whether hylobatid divergence was more basal than currently supported.